Speech and Brain Mechanisms - Penfield, Wilder, 1891-1976; Roberts, Lamar (Vanuxem lectures, 2014)
The outcome of ten years' work, this book is a carefully planned study of brain dominance, aphasia, and other speech disturbances, and includes a discussion of the cerebral mechanisms of speech and the learning and teaching of language.